WAYS TO INCREASE ENVIRONMENTAL ACTIVITY OF STUDENTS IN THE CONDITIONS OF CLIMATE CHANGE (Scientific journal of the Fergana State University, 2024)
In the article, it is not a secret to anyone that increasing the environmental activity of students in the conditions of global climate changes is the most urgent issue today, because the atmospheric air is flooded with various harmful gases and dust particles as a result of the rapid development of industrial enterprises and the increase in the number of cars. due to sudden changes in weather and its serious impact on human health and causing a number of other problems as a result of deterioration of the quality of agricultural crops. It is intended to understand the impact of climate change, assess its dangerous consequences, prevent it, introduce measures to adapt to the conditions of climate change in Uzbekistan to the population and students, and implement them in practice.